Climate Change and Health: Essay on the Limits of Naturalism - Lencastre, Marina Prieto Afonso (2023)
One of the main problems of the twenty-first century is climate change and its impacts on global health. Nonetheless, there is a certain optimism that is rooted in the new world opened up by the possibilities of technoscience, namely in the control of health and climatic and environmental hazards. But on the horizon of these possibilities, there are increasingly clear signs that technological and scientific naturalism alone is running out of capacity to contain its own challenges. Naturalism has problems in resolving climate change impacts on health, founding ethics and epistemology, and defining relations with non-humans. In an era that is largely dependent on the actions that result from our thinking, there is a call to imagine multiverses or different versions of what naturalism seems to present as a single reality. This essay aims to explore the limits of naturalism to address climate change health hazards.